The questionable legitimacy of non-state anti-corruption bodies: a case study of the Tennis Integrity Unit - Harkin, Diarmaid (Crime, law and social change, 2017)
The rise of non-state governance to tackle corruption, social harm and misbehaviour within globalised industries often produces key questions about the credibility and effectiveness of ‘private’ enforcement. This articles uses the case study of the ‘Tennis Integrity Unit’ (TIU) to explore the struggles of non-state, transnational anti-corruption bodies to build and maintain legitimacy. Heightened media attention and specific allegations of complacent, under-enforcement against match-fixing in January 2016 highlighted the deficit of trust in the TIU which has prompted a review of the industry’s anti-corruption efforts. While non-state governance bodies are always likely to be considered suspect, there are specific ways in which such bodies, including the TIU, can attempt to improve their legitimacy through enhancing transparency, embracing forms of ‘meta-regulation’ and appreciating the ‘dialectic’ nature of legitimacy through expanding the involvement and participation of key stakeholders.